Formal Modeling and Analysis of Timed Systems : 15th International Conference, FORMATS 2017, Berlin, Germany, September 5-7, 2017, Proceedings /: 15th International Conference, FORMATS 2017, Berlin, Germany, September 5-7, 2017, Proceedings. (2017) - Unknown
No abstract available